2004
DOI: 10.1093/sleep/27.4.741
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Sleep Spindles and Spindle Activity in Midlife Women with Fibromyalgia and Pain

Abstract: Women with FM and pain have fewer sleep spindles and reduced electroencephalogram power in spindle frequency activity compared to control women of similar age. These data imply that some aspect of thalamocortical mechanisms of spindle generation might be impaired in FM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 0 publications
2
54
0
2
Order By: Relevance
“…Of 320 patients who were screened, 209 underwent PSG and 195 were randomized. Of 125 patients who failed screening, the most common reasons for failure were thyroid stimulating hormone test results being out of range (24), withdrawal of consent (18), sleep apnea or Apnea Hypopnea Index out of range (16), inability to discontinue current compromising drugs (12), did not meet PVAS criteria or ACR criteria for FM (12), lost to followup (7), and other pain disorders (6). No other screening failure reason included more than 4 subjects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 320 patients who were screened, 209 underwent PSG and 195 were randomized. Of 125 patients who failed screening, the most common reasons for failure were thyroid stimulating hormone test results being out of range (24), withdrawal of consent (18), sleep apnea or Apnea Hypopnea Index out of range (16), inability to discontinue current compromising drugs (12), did not meet PVAS criteria or ACR criteria for FM (12), lost to followup (7), and other pain disorders (6). No other screening failure reason included more than 4 subjects.…”
Section: Methodsmentioning
confidence: 99%
“…The anomaly was not reported in a recent small-scale study that focused on the presence of alpha EEG during a selected component of non-REM sleep, i.e., delta EEG sleep [or slow-wave sleep (SWS)] 15 . Other reported alterations are a reduction in stage 2 sleep spindles 16 , shorter duration of stage 2 sleep periods 17 , and a high frequency of cyclical alternating pattern (CAP) 18 . CAP is a periodic EEG sleep phenomenon that is an objective physiological measure of the stability of sleep.…”
mentioning
confidence: 99%
“…Some studies showed a reduction in stage N2 sleep spindles and in stage N2 sleep periods [38,39]. Another study found a high frequency of cyclic alternating pattern (CAP) [40], which is a periodic EEG sleep phenomenon that provides physiological measure of sleep stability.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using PSG have indicated that chronic pain patients have more microarousals, more body movements during sleep, more frequent transitions between the sleep stages with increased N1 and N2 sleep and reduced N3 and N4, frequent awakenings, and lower SE, compared to healthy volunteers [ 49 , 50 ]. Sleep disruption experienced by these patients is also characterized by reduced spindle activity at N2 sleep [ 51 ], an increase in the rate of cyclic alternating pattern (CAP); [ 52 ] a lack of heart rate variability reduction [ 53 ] and an intrusion of electroencephalographic (EEG) activity in the alpha range (8-13 cps) during NREM sleep [ 54 ]. Although alpha-delta sleep was once thought to be a signature of pain-related sleep disturbance [ 55 ], there is now confl icting evidence suggesting otherwise [ 56 -59 ].…”
Section: Scientifi C Relevance To Pain Care Prevalence and Pattern Ofmentioning
confidence: 98%